2005
DOI: 10.1152/ajpcell.00045.2005
|View full text |Cite
|
Sign up to set email alerts
|

Novel lipid mediator aspirin-triggered lipoxin A4 induces heme oxygenase-1 in endothelial cells

Abstract: -Lipoxins (LX) and aspirintriggered LX (ATL) are eicosanoids generated during inflammation via transcellular biosynthetic routes that elicit distinct anti-inflammatory and proresolution bioactions, including inhibition of leukocytemediated injury, stimulation of macrophage clearance of apoptotic neutrophils, repression of proinflammatory cytokine production, and inhibition of cell proliferation and migration. Recently, it was reported that aspirin induces heme oxygenase-1 (HO-1) expression on endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 54 publications
7
65
0
Order By: Relevance
“…This finding is in line with many studies that link HO-1 to anti-inflammatory features (Wagener et al, 2003) and is strengthened by observations made in the case of HO-1 deficiency (Yachie et al, 1999). Two recently published studies (Grosser et al, 2003;Nascimento-Silva et al, 2005) showing the ability of aspirin to induce HO-1 in ECV304 also support our data.…”
supporting
confidence: 93%
“…This finding is in line with many studies that link HO-1 to anti-inflammatory features (Wagener et al, 2003) and is strengthened by observations made in the case of HO-1 deficiency (Yachie et al, 1999). Two recently published studies (Grosser et al, 2003;Nascimento-Silva et al, 2005) showing the ability of aspirin to induce HO-1 in ECV304 also support our data.…”
supporting
confidence: 93%
“…33 In addition, ATL-1 induces HO-1 in human endothelial cells, revealing an undescribed mechanism for the antiinflammatory activity of these lipid mediators. 34 Another study has discovered that protectin D1 regulates HO-1 in a renal model. 35 HO-1, which is a rate-limiting enzyme that metabolizes heme accumulates in tissues because of blood red cell turnover, is correlated with the production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that this mechanism is mediated by the activation of the G protein-coupled lipoxin A 4 receptor (Nascimento-Silva et al, 2005). It has been suggested that aspirin-triggered lipoxin induces HO-1 in human endothelial cells and that this increase in HO-1 protein is responsible for the antiinflammatory activity of these lipid mediators Nascimento-Silva et al, 2005).…”
Section: G Cardiovascular Drugs and Drug Developments Targeting Hemementioning
confidence: 99%